Ultraporous poly(lactic acid) scaffolds with improved mechanical performance using high‐pressure molding and salt leaching. Issue 5 (25th June 2013) - Zhang, Jin; Yan, Ding‐Xiang; Lei, Jun; Xu, Jia‐Zhuang; Hsiao, Benjamin S.; Li, Zhong‐Ming
ABSTRACT A novel processing technique, i.e. high‐pressure compression molding/salt leaching, was developed to fabricate ultraporous poly(lactic acid) (PLA) scaffolds. The optimized composition was studied in relation to the porosity, pore morphology, thermal property, and mechanical performance of the PLA scaffolds. At a porogen (CaCO3) content of 90 wt %, the scaffolds have an interconnected open pore structure and a porosity above 80%. It was truly interesting that the structural stability of high‐pressure molded scaffolds was remarkably improved based on the fact that its glass transition temperature (83.5°C) increased about 20°C, as compared to that of the conventional compression‐molded PLA (60°C), which is not far from physiological temperature (∼37°C) at the risk of structural relaxation or physical aging. More importantly, the mechanical performance of PLA scaffolds was drastically enhanced under optimized processing conditions. At pressure and temperature of 1000 MPa and 190°C, the porous PLA scaffolds attained a storage modulus of 283.7 MPa, comparable to the high‐end value of trabecular bone (250 MPa) ever reported. In addition, our prepared PLA scaffolds showed excellent cellular compatibility and biocompatibility in vitro tests, further suggesting that the high‐pressure molded PLA scaffolds have high potential for bone tissue engineering applications. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 3509–3520, 2013